'A brilliancy of their own': Female Art, Beauty and Sexuality in Charlotte Brontë's Jane Eyre. (2nd October 2018) - Ioannou, Maria
Abstract : This article studies the portraits of Rosamond Oliver and Blanche Ingram in Charlotte Brontë's Jane Eyre, to argue that, first, the portraits participate in the nineteenth-century dialogue about women in art and, second, capture Jane's convictions on the theme of sexual love. This is especially so in the case of Rosamond's miniature, which comes at a point where Jane has resolved to choose a sexual union rather than a loveless marriage. In an important sense, Jane is Rosamond; the subject (artist) identifies with the object (model) in an equation of female beauty with agency and capacity for sexual feeling.